Oxazolidinone antibiotics impair ex vivo megakaryocyte differentiation from hematopoietic progenitor cells and their maturation into platelets - Milosevic, TV; Vertenoeil, G; Vainchenker, W; Tulkens, PM; Constantinescu, SN; Van Bambeke, F (American Society for Microbiology, 2024)
Oxazolidinones (linezolid and tedizolid) adverse reactions include thrombocytopenia, the mechanism of which is still largely unknown. In cultured cells, oxazolidinones impair mitochondrial protein synthesis and oxidative metabolism. As mitochondrial activity is essential for megakaryocyte differentiation and maturation into platelets, we examined whether oxazolidinones impair these processes ex vivo and alter, in parallel, the activity of mitochondrial cytochrome c-oxidase (CYTOX; enzyme partly encoded by the mitochondrial genome) and cell morphology. Human CD34+ cells were isolated, incubated with cytokines (up to 14 days) and clinically relevant oxazolidinone concentrations or in control conditions, and used for (i) clonogenic assays [counting of megakaryocyte (CFU-Mk), granulocyte-monocyte (CFU-GM), burst-forming unit-erythroid (BFU-E) colonies]; (ii) the measure of the expression of megakaryocyte surface antigens (CD34 to CD41 and CD42); (iii) counting of proplatelets; (iv) the measurement of CYTOX activity; and (v) cell morphology (optic and electron microscopy). Oxazolidinones caused a significant decrease in BFU-E but not CFU-Mk or CFU-GM colonies. Yet, the megakaryocytic lineage was markedly affected, with a decreased differentiation of CD34+ into CD41+/CD42+ cells, an abolition of proplatelet formation and striking decrease in the numbers of large polylobulated nucleus megakaryocytes, with a complete loss of intracellular demarcation membrane system, disappearance of mitochondria, and suppression of CYTOX activity. These alterations were more marked in cells incubated with tedizolid than linezolid. These data suggest that oxazolidinones may induce thrombocytopenia by impairing megakaryocytic differentiation through mitochondrial dysfunction. Pharmacological interventions to prevent this toxicity might therefore be difficult as mitochondrial toxicity is most probably inherently linked to their antibacterial activity.